Legitimation of law in juridical discourse - A. V. Skorobogatov; A. A. Malik (Russian Journal of Economics and Law, 2019)
Objective: to study the philosophical and social mechanisms of legitimization of law in the modern legal discourse. Methods: the methodological basis of the study is the concept of legal discourse by Y. Habermas, which allows considering the said issue in the context of legal interaction between the state and society, taking into account the modern trends of social and legal development.Results: it is concluded that the process of legitimization of law under modern conditions is of a conventional nature, implying the establishment of mutual rights and obligations of the state as a lawmaker and the society as a subject and object of state activity. As a subject, the society provides legal discourse with the necessary interpretation of social needs and forms a legitimate image of law, the implementation of which is based on socially active behavior of citizens. As an object, the society is the key element of the goal-setting of state law-making aimed at the creation and maintenance of security and legal order. The legislative activity and law enforcement acquire the necessary legitimacy only when the state’s perceptions of the images of objective and subjective social needs are identical.Scientific novelty: based on the discourse analysis of social development, the features of the law legitimization mechanism under modern conditions are revealed. In particular, the law created by this mechanism will be characterized by the following features: a) it acts as an intermediary in the interaction between the political system and a person (public administration and the economic system); b) it acts as a system of rules governing relations between the state and society at individual and normative levels of legal regulation. The legal norms establishing prohibitions must be justified in terms of moral and political discourse. This justification becomes an element of their legitimization and indicates the achievement of social consensus in relation to the claims of the state to its right/duty to form and maintain public security and the rule of law. Practical significance: the main provisions and conclusions of the article can be used in scientific and pedagogical activity when considering the nature and content of legal development.